Crohn's Disease Diagnosed in a Man with Sarcoidosis: Coincidence or Correspondence?. (27th May 2022) - Mills, Krystal; Fatima, Shaheen; Fas, Norberto
Abstract : Crohn's disease and sarcoidosis are characterized by noncaseating granulomas, but rarely do they present in the same patient. Their coexistence presents a diagnostic challenge as they are often classified as clinically separate, despite their similarities. We present a case of a 59-year-old man previously diagnosed with pulmonary sarcoidosis who presented to the emergency room with abdominal pain and diarrhea. Colonoscopy revealed multiple ulcers in the colon, with histology in keeping with newly diagnosed Crohn's colitis. The patient had a good clinical response to initiation of steroid therapy and a tumor necrosis factor (TNF) inhibitor.